Electrocardiogram interpretation skills among healthcare professional and related factors: A Review on Myocardial Infraction cases - Dwi Prihatiningsih; Alison Hutton (Journal of Health Technology Assessment in Midwifery, 2018)
Acute Coronary Syndrome (ACS) is a major cause of death and disability worldwide. In spite of the advance of many other diagnostic techniques of biomarkers and imaging, the 12-lead electrocardiogram (ECG) remains the gold standard for early identification and management of ACS. The aim of this study was to determine the HCPs interpretation skills on 12 lead ECG especially in Myocardial Infarction cases. Primary research of ECG interpretation skill of HCPs and related factors were identiﬁed by searching electronic databases and bibliographies. Sixteen articles were identified based on inclusion and exclusion criteria. Variations were found on ECG interpretations among HCPs. Moreover it was found that training, experience seniority and AMI mimicking pattern influence ECG interpretation skills among HCPs and decision making for thrombolytic therapy.